2019
DOI: 10.1016/j.yfrne.2019.100787
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms and cellular events involved in the neuroprotective actions of estradiol. Analysis of sex differences

Abstract: Estradiol, either from peripheral or central origin, activates multiple molecular neuroprotective and neuroreparative responses that, being mediated by estrogen receptors or by estrogen receptor independent mechanisms, are initiated at the membrane, the cytoplasm or the cell nucleus of neural cells. Estrogen-dependent signaling regulates a variety of cellular events, such as intracellular Ca 2+ levels, mitochondrial respiratory capacity, ATP production, mitochondrial membrane potential, autophagy and apoptosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 266 publications
1
62
0
4
Order By: Relevance
“…In the brain, there is much evidence that estrogen has a role in neuroprotection (Arevalo, Azcoitia, Azcoitia, & Garcia-Segura, 2015;Azcoitia, Barreto, Barreto, & Garcia-Segura, 2019;Cui, Shen, Shen, & Li, 2013;Genazzani, Pluchino, Pluchino, Luisi, & Luisi, 2007).…”
Section: Estrogen-far More Than a Sex Hormonementioning
confidence: 99%
“…In the brain, there is much evidence that estrogen has a role in neuroprotection (Arevalo, Azcoitia, Azcoitia, & Garcia-Segura, 2015;Azcoitia, Barreto, Barreto, & Garcia-Segura, 2019;Cui, Shen, Shen, & Li, 2013;Genazzani, Pluchino, Pluchino, Luisi, & Luisi, 2007).…”
Section: Estrogen-far More Than a Sex Hormonementioning
confidence: 99%
“…Furthermore, the X chromosome contains 10% of microRNA in the human genome as compared to 2 on the Y chromosome and the X linked microRNA leads to much higher immune responses in female participating in sex differentiated immunity [33]. Authophagy may be another of the dysregulated basic cellular processes [34] involved in the pathogenesis of allergies. Estradiol regulates autophagy in several cell types and may activate the phosphoinositide 3-kinase (PI3K)/Akt pathway [35,36].…”
Section: Hormones Chromosomes Immunity and Allergymentioning
confidence: 99%
“…We next sought to determine whether pretreatment with 17β-Estradiol (E2), a multifaceted, estrogen receptor-dependent (and independent) neuroactive hormone (Azcoitia et al, 2019), might ameliorate the elevated CC3-mediated cortical apoptosis in Arx (GCG)10+7 , thus providing a mechanism for its early protective effect. Previously, we showed that E2 treatment reduces neonatal spasms and aberrant electrographic phenotypes including seizures and interictal discharge in adults when administered daily during the first week of life, but not later in adult Arx (GCG)10+7 mutants (Olivetti et al, 2014).…”
Section: Early Hormone Therapies Modulate Interneuron Density But Notmentioning
confidence: 99%